Evaluation of Handwritten Answer Scripts Using Machine Learning Approaches (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Learning is the fundamental aspect for human beings to gain knowledge. Educating students to learn and to give assessment to check their ability plays an important role. Examination is the key to evaluate he/she scored. students work is a central aspect of the teachers in term of evaluation. Though multiple criteria affect the assessing of student’s work. Also, there are several time-consuming process that affects the departments like lot of answer scripts to evaluate, marking mistakes, errors in totalling. so, we are developing a robust tool to automate the short answer using machine learning techniques. There are two modules in the first module we use OCR to extract handwritten answer from the answer script and word is recognized. In the second module, handwritten answer is evaluation is done with this approach, computational time of manual processing can be reduced. Finally, the result gained is 90 percent.